Integrating geospatial techniques and field survey to assess the changing nature of meander movements and meander geometry of Raidak-I River in the Himalayan foothills, West Bengal - Hasanuzzaman, Md.; Hasan Mandal, Mehedi; Mandal, Sujit (Bulletin of Geography. Physical Geography Series, 2022)
Channel migration and resultant meander movements are the two important fluvial processes found in the riparian environment of a river basin. The present research explores the changing nature of the meander movements and meander geometry of the Raidak-I River in the Himalayan foothill region using geospatial tools. The study incorporated Landsat data (satellite imageries) for the years 1972, 1980, 1988, 2004, 2012 and 2021 and the whole study has been segmented into five periods i.e., 1972–1980, 1980–1988, 1988–2004, 2004–2012 and 2012–2021 to examine which type of meander movement dominates in the Raidak-I River within a particular time frame and how the nature of the meander movements is being changed over time. Bank lines of different periods have been superimposed with the help of the overlay analysis method in ArcGIS software (Version 10.8) to obtain the results. Furthermore, Arc-Extension tools have also been used to measure the meander geometry. Twelve active river bends have been identified to study meander geometry of sinuosity indices, meander length, meander width, meander-ratio, channel width and radius of curvature from 1972 to 2021. Initially, lateral movements predominated but, in the late-stage, rotational movement became much more prominent, which indicates dynamicity of the river channel in recent time. The cross-sectional study revealed that a convex bank has frequently been replaced with a concave bank and vice versa. The study finds human intervention – especially the construction of embankments – is the main reason behind such meander dynamics. The method we have used here is very simple, and thus can be considered for any part of the world and is very beneficial for identifying suitable sites for embankment construction, river restoration and channel management.